The Impact of Remittance of Dayak Migrant Workers on Socio-Economic Conditions: Evidence from West Kalimantan, Indonesia - Pitalis Mawardi Baging (Syntax Literate, 2023)
The purpose of this study was to explore the impact of remittance on the socio-economic conditions of Dayak communities in West Kalimantan, Indonesia, including social economic life before, during, and after becoming a migrant worker in Malaysia. seven of the 50 Dayaks were pleased to be interviewed. Data from semi-structured in-depth interviews, participants recalled their experiences of working in overseas and their shared views on being migrant workers. The interviews were audio-recorded, transcribed and analyzed using a typical method of qualitative content analysis. To strengthen the findings of the interview, seven neighbors were also interviewed. The findings of the study show that the lives of the Dayak workers before becoming migrant workers were all lacking, they were still not able to meet the family's needs. However, when he became a migrant worker, his soci-economic life became better. During working in Malaysia, it is not as smooth as expected, they are imprisoned and even deported because they do not have official permission. because, they did not return to being workers, and chose to become entrepreneurs and oil palm farmers in their villages.